Factors influencing consumer buying behaviour in luxury goods markets. - Khudyakova, Ekaterina (2025)
This thesis explores factors influencing consumer buying behavior in luxury goods markets. The thesis aims to identify the main factors that shape and influence consumer purchasing preferences in luxury goods markets. Another sub-objective is to find out which features in the purchasing behavior in the luxury goods market are characteristic for Generation Z and Generation Y and then to compare them. Through quantitative research, information will be gathered regarding the factors influencing the decision-making process of the Generation Z and Y consumers in case of luxury goods, which will then be evaluated. The thesis is divided into a theoretical and a practical part. In the theoretical part, the reader will be introduced to general information regarding the luxury industry, a description of Generation Z's and Generation Y's consumer behavior, and factors influencing purchasing consumer behavior. The second part, the practical part, aims to understand how Generation Z and Y consumers make decisions about purchasing luxury goods by conducting questionnaire-based research to explore the influencing factors. The contribution of the thesis is an overall assessment of the factors influencing consumer buying behavior from the perspective of consumers in case of luxury goods. Based on these results, the thesis formulates conclusions and recommendations that may serve as a foundation for future research in the field of consumer behavior among Generations Y and Z. The findings can also support luxury brands in making strategic decisions and shaping their market approach in line with the specific characteristics of these two generations.